Tindakan Kekerasan Dalam Sistem Hukum di Indonesia: Studi Kasus Putusan Nomor 899/pid.Sus/2023.Pn Medan - Puspita, Della; Saragih, Rinnauli; Rahmawati, Sellia; Haykal Parapat, Tegar Alif; Gabriel Siahaan, Parlaungan; Batu, Dewi Pika Lumban (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2023)
Violence is becoming more common as society, technology, and human individualism develop. In this study, acts of violence against people or objects together in public occurred one day, Sunday, February 19, 2023, at approximately 02.15 WIB. carrying out a brawl on the Titi Besi Bridge (Bridge 39), which is on Jalan Yong Panah Hijau, Environment V, Labuhan Deli Village. Based on this case, the problem that the author wants to study is: what are the stages in the process of criminal acts of violence against people or property in the Medan District Court based on the procedural law in Decision Number 899/Pid.Sus/2023/Pn Mdn, and what is the decision of the Council? The judge is in accordance with the laws that regulate acts of violence, one of which is Article 170 Paragraph 1. In this research, the method used is qualitative, namely juridical-normative, which means that this legal research only uses secondary data or related library materials, and the data collection technique used is examining the results of Decision Number/899.Pid.Sus/2023/Pn Mdn and also related books and journals. The aim is to obtain an in-depth understanding and theoretical basis regarding the problem being researched. In the verdict of the crime of violence against the defendant Muhammad Saidi Amri Number (899.Pid.Sus/2023/Pn Mdn), he was proven to have violated Article 170 Paragraph (1) and received a prison sentence of 2 years in prison, including a period of detention and arrest. So it is not in accordance with Article 170 Paragraph (1), which states that if someone commits a criminal act of violence openly in public, he will be sentenced to 5 years and 6 months.